KEANEKARAGAMAN BINTANG LAUT (Asteroidea) DI PANTAI LAMALAKA KECAMATAN ILE BOLENG KABUPATEN FLORES TIMUR - Yunita Rambu Mbana; Yanti Daud; Novi I. Bullu (Indigenous Biologi : Jurnal Pendidikan dan Sains Biologi, 2020)
Sea star is an invertebrate animal that is included in the phylum Echinoderms from the Asteroidea class. Radial symmetry is shaped and generally has five or more arms and does not have a frame that helps movement. This study aims to determine the diversity of sea star (Asteroidea) in Lamalaka Beach, Ile Boleng District, East Flores Regency.This research will be conducted in July-August 2019, the location of the study is on the Lamalaka coast, Ile Boleng District, East Flores Regency.The method used is a survey method, based on the presence of Asteroidea species that are considered to represent the area. The steps in data collection are field survey, observation, identifying species in each plot, observing and recording their marphological characteristics.Sampling uses the technique of determining the location of sampling using Area sampling. To identify based on Human and Deloach identification guidelines, 2010. Analysis of the data used in this research is quantitative descriptive and the composition of Asteroidea species can be stated based on visual observations calculating species density, relative density, and dominance index, diversity.Based on the results of the study, found 4 species of Asteroidea, namely Protoreaster nodulosus, Linckia laevigata, Echinaster luzonicus, Astropecten polyacanthus. The highest species density calculation results were found in P. nodulosus species with a value of 0.78 ind / m2. while the lowest species density was found in L.laevigata species with a value of 0.63 ind / m2. The highest relative density was found in P. nodulosus species with a value of 27.64%, and the lowest relative density found in L.laevigata species with a value of 22.35 %. The index of starfish species dominance in Lamalaka Beach, obtained a value of D <0.5, indicates that there are no species that dominate in Lamalaka Beach. The existence of starfish in Lamalaka Beach, Ile Boleng District, East Flores Regency needs to be preserved. One form of effort to preserve it is to conduct monitoring with routine monitoring to monitor the condition of the sea star population in these waters. Besides that, it is also necessary to increase the utilization of sea stars as one of the natural tourism objects and as an Ecoedutourism tourism object. Thus, the presence of starfish will be felt by the wider community so that awareness to maintain the existence of starfish will be increased.